Analysis of Incidence of Human with Larvae Helminthiases (Echinococcosis, Toxocariasis, Dirofilariasis) in the Russian Federation - L. A. Ermakova; T. I. Tverdokhlebova; S. A. Nagorny; N. Yu. Pshenichnaya; K. Kh. Boltachiev (Эпидемиология и вакцинопрофилактика)
The paper presents the literature data analysis and statistical reports on the population morbidity of larval helminthiases in Russian Federation over the past 20 years. Epidemiological aspects of larval helminthiases in areas with different climatic, geographic and socio-economic conditions were determined.